Capillary growth, ultrastructure remodelling and exercise training in skeletal muscle of essential hypertensive patients - Gliemann, L.; Buess, R.; Nyberg, M.; Hoppeler, H.; Odriozola, A.; Thaning, P.; Hellsten, Y.; Baum, O.; Mortensen, S. P. (Acta Physiologica, 2015)
Aim The aim was to elucidate whether essential hypertension is associated with altered capillary morphology and density and to what extent exercise training can normalize these parameters. Methods To investigate angiogenesis and capillary morphology in essential hypertension, muscle biopsies were obtained from m. vastus lateralis in subjects with essential hypertension (n = 10) and normotensive controls (n = 11) before and after 8 weeks of aerobic exercise training. Morphometry was performed after transmission electron microscopy, and protein levels of several angioregulatory factors were determined. Results At baseline, capillary density and capillary‐to‐fibre ratio were not different between the two groups. However, the hypertensive subjects had 9% lower capillary area (12.7 ± 0.4 vs. 13.9 ± 0.2 μm2) and tended to have thicker capillary basement membranes (399 ± 16 vs. 358 ± 13 nm; P = 0.094) than controls. Protein expression of vascular endothelial growth factor (VEGF), VEGF receptor‐2 and thrombospondin‐1 were similar in normotensive and hypertensive subjects, but tissue inhibitor of matrix metalloproteinase was 69% lower in the hypertensive group. After training, angiogenesis was evident by 15% increased capillary‐to‐fibre ratio in the hypertensive subjects only. Capillary area and capillary lumen area were increased by 7 and 15% in the hypertensive patients, whereas capillary basement membrane thickness was decreased by 17% (P < 0.05). VEGF expression after training was increased in both groups, whereas VEGF receptor‐2 was decreased by 25% in the hypertensive patients(P < 0.05). Conclusion Essential hypertension is associated with decreased lumen area and a tendency for increased basement membrane thickening in capillaries of skeletal muscle. Exercise training may improve the diffusion conditions in essential hypertension by altering capillary structure and capillary number.